ANALYSIS OF THE INFLUENCE OF GIVING REWARDS AND ICEBREAKERS ON THE LEARNING PROCESS AT SDN 04 KARANGTENGAH - Putri Kania, Intan; Febriani P, Resnawati; Nurulaeni, Fitria (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
The learning process should be an activity for students to build their understanding. Even so, there are still many students who look bored and lack enthusiasm. An attempt that needs to do by the teacher is to give rewards and icebreakers. This paper discusses the influence of giving rewards and icebreakers on the learning process at SDN 04 Karangtengah in Cibadak Sukabumi. This paper used qualitative research with teachers and fourth-grade students as the research subjects. Data collection was carried out through observation and interview techniques with research instruments in the form of observation and interview sheets. The results indicate that giving rewards and icebreakers had a significant influence on the learning process for four-grade students at SDN 04 Karangtengah. Thus, giving rewards and icebreakers are able to arouse students’ learning motivation and it also has an impact on students’ cognitive learning outcomes. Giving rewards and icebreakers can produce students’ enthusiasm for learning. Learning also becomes more competitive, collaborative, and varied so that students return to concentrate and actively participate in learning.